The effect of Japanese eel as a main ingredient on hair condition, antioxidant ability, apparent total tract digestibility and body weight gain in cat food - Yuan, Yilin; Zhu, Leilei; Cai, Xuan; Mao, Hui; Wang, Tingting; Tao, Shengqing; Bao, Jiayu; Liu, Chengyin; Feng, Jie (Frontiers in Veterinary Science, 2025)
This study aims to evaluate the impact of Japanese eel (Anguilla japonica) as a primary ingredient in cat food on hair condition, antioxidant capacity, apparent total tract digestibility (ATTD), and body weight gain in adult cats. Twenty-four healthy adult cats were assigned divided into three dietary groups: a 0% eel group (C), a 14% eel group (T1), and a 40% eel group (T2). Over a 56-day period, hair coat condition, ATTD, antioxidant indices, and body weight were monitored. The results indicated an improvement in hair luster and softness among the high eel group. By day 56, the 40% eel group demonstrated significant improvements in both hair luster (3.0 vs. 2.4 in control, p < 0.05) and softness (3.0 vs. 2.2 in control, p < 0.05). Scanning Electron Microscopy (SEM) analysis confirmed a significant reduction in hair scale thickness for the 14% (39.36% reduction) and 40% eel groups (46.80% reduction) compared to the control group (p < 0.05). The ATTD of calcium was significantly higher in both eel groups (71.3% for T1 and 74.1% for T2 vs. 62.8% in control, p < 0.05); however, no significant differences were observed regarding crude fat or protein digestibility (p > 0.05). Serum antioxidant capacity was notably enhanced in the 14% eel group, with a 23% increase in total antioxidant capacity (T-AOC) and a 15% increase in superoxide dismutase (SOD) activity compared to the control (p < 0.05). Furthermore, glutathione (GSH) content was higher, and malondialdehyde (MDA) levels were lower in the eel groups; however, these differences did not reach statistical significance (p > 0.05). Notably, body weight gain showed a slight downward trend in the eel groups, with average daily gain recorded at 2.1 g/day for T2 versus 2.4 g/day for the control group, though this difference was not significant (p > 0.05). Fecal scores remained consistent across all experimental groups, indicating no adverse effects on fecal quality (p > 0.05). These findings suggest that incorporating Japanese eel into cat food can enhance hair coat condition and antioxidant capacity without adverse effects on body weight or fecal quality. Therefore, it is recommended to include a 14% level for optimal benefits.